Perencanaan Gedung Perkuliahan Lantai Lima Kampus Universitas Dr. Soetomo Menggunakan Stuktur Baja: (Studi Kasus : Gedung I Universitas DR. Soetomo) - Fadlur Rochman Irgi Feriawan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The rapid advancement of science and technology requires universities to provide safe, comfortable, and representative learning facilities. One such initiative is the construction of a five-story lecture building at Dr. Soetomo University, designed with a steel structure as an alternative to reinforced concrete. Steel was chosen due to its high tensile strength, uniform material properties, lighter weight, ease of installation, and strong resistance to earthquake loads. This study aims to design a five-story lecture building with a steel structure that meets the requirements of strength, stability, and safety in accordance with applicable standards. The method applied is structural planning based on SNI 1729:2020, SNI 1727:2020, and SNI 1726:2019 using the Load and Resistance Factor Design (LRFD) approach. Structural analysis was conducted with SAP2000 version 2014 through three-dimensional modeling that considers geometry, material properties, loading, and placement. The results show that the selected steel profiles for beams, columns, and connections are capable of supporting the combination of dead loads, live loads, and seismic loads with safe performance. The maximum stress remains below the allowable limit, and the deflection values do not exceed the permitted deviation. These findings confirm that steel provides efficiency in dimensions and materials while offering practicality and earthquake resistance, and the design produced can serve as a useful reference for future multi-story building projects in earthquake-prone regions.